P227 Reduced respiratory muscle strength, lung function, and functional status and symptomology in patients referred to Long COVID clinics, an observational cohort analysis. (11th November 2022) - Faghy, MA; Ashton, REM; Owen, R; Yates, J; Thomas, C; Maden-Wilkinson, T; Kumar, S; Gururaj, R; Ozemek, C; Arena, R; Bewick, T
Abstract : Introduction: One in ten people will develop Long COVID (LC) following infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Despite broad-ranging and episodic symptomology, there are no data that demonstrate changes in functional status (FS), respiratory muscle strength and lung function over time. We conducted a sixteen-week cohort observation of LC patients to determine changes in FS, respiratory muscle strength and lung function. Method: Sixty-six patients (n=48 females, mean age 51 ± 10 years, n=8 hospitalised, mean time post-infection 6.2 ± 1.8 months) were recruited from LC clinics in the United Kingdom (CPMS ID: 52331). Patients completed five face-to-face visits (day 0, 28, 56, 84 and 110 ± 3 days) and bi-weekly telephone consultations (day 14, 42, 70 and 98 ± 3 days). FS was assessed via the post-COVID functional status scale (PCFS) and the six-minute walk test (6MWT). Maximum inspiratory (MIP) and expiratory (MEP) respiratory muscle pressure and lung function (forced vital capacity (FVC) and forced expired volume in one second (FEV1 ) were assessed during face-to-face visits according to published standards. Results: PCFS was 2.7 ± 0.4 AU, P=0.02 at baseline and improved at 16-weeks (2.1 ±1.1 AU) and still highlighted impaired FS. 6MWT was 322 ± 133 meters at baseline and improved at 16 weeks (430 ± 150 meters, P<0.01) but remained lower than normative values for healthy age-matched controls. MIP was 77 ± 21 cmH2 O at baseline (86% predicted) and was unchanged post 16 weeks (88 ± 25 cmH2 O, 92% predicted, P>0.05). Baseline MEP was 115 ± 41 cmH2 O (96% and was unchanged post-16-weeks (119 ± 48 cmH2 O, 92% predicted, P>0.05). Lung function data were below predicted values and unchanged over 16 weeks (baseline FVC: 3.10 ± 0.53 L.s -1, 72% predicted, post 16 weeks: 3.16 ± 0.34 L.s -1, 73% predicted, P> 0.05 and baseline FEV1 : 2.68 ± 0.39 L.s -1, 85% predicted, post 16 weeks: 2.75 ± 0.36 L.s -1, 85% predicted). Conclusion: LC patients demonstrate reduced respiratory muscle strength and lung function which could be associated with reduced FS and should be addressed via specific rehabilitation approaches. Please refer to page A216 for declarations of interest related to this abstract.